Expectation formation under uninformative signals - Kieren, Pascal; Weber, Martin (SSRN, 2022)
How do individuals process non-diagnostic information? According to Bayes’ Theorem, signals which do not carry relevant information about the objective state of the world are treated as if no signal occurred. This paper provides experimental evidence that individuals update their expectations even after observing uninformative signals. Importantly, the direction in which they update depends on the valence of the signal. Prior beliefs become more optimistic after desirable uninformative signals and more pessimistic after undesirable uninformative signals. Our results provide novel insights why individuals form and entertain false beliefs in environments where potentially new information is easily accessible but costly to verify (e.g. online media)